Classic Grounded Theory: A Rigorous Methodology for Research Involving Participants With Severe/Profound Intellectual Disabilities: A Discussion of Classic Grounded Theory as a Way of Undertaking Rigorous, Credible Research Involving Participants With Severe/Profound Intellectual Disability - Martin, Anne‐Marie; Nilsson, Lisbeth; Andrews, Tom (British Journal of Learning Disabilities, 2025)
Background: Including people with severe/profound intellectual disabilities as research participants challenges researchers due to their diverse abilities to participate and express themselves. Ensuring the rigour of the research and the credibility of the findings presents a challenge. Methods: We use examples from our research to demonstrate that Classic Grounded Theory offers a systematic but flexible way of undertaking rigorous, credible research that can involve participants with severe/profound intellectual disability. Findings: Examples from our research show that full and adherent application of Classic Grounded Theory enabled us to generate a multivariate theory at the explanatory level. Rigorous adherence to and application of this methodology and in‐depth analysis of video data unveiled subtle interaction and communication behaviours, as well as the development of tool‐use understanding. Conclusion: It is important that people with severe/profound intellectual disabilities are included in research, so their experiences inform the knowledge and evidence guiding and shaping their care and support. Classic Grounded Theory provides a credible, rigorous research methodology for inclusion of people that may otherwise be excluded as participants. Summary: Research methods can sometimes exclude people with severe/profound intellectual disability due to their diverse abilities to participate and express their perspectives.It is important to find ways to enable their participation and capture their expressions, so their own 'voice' can inform their care and support.Classic Grounded Theory is one way of doing research. It looks at what people do or their behaviour to understand how they experience their world.We argue that Classic Grounded Theory can provide researchers with an opportunity to undertake quality research with people with severe/profound intellectual disabilities.